Analisa Probalitas Pemanfaatan Pompa Irigasi untuk Areal Persawahan Desa Waimital Kecamatan Kairatu Kabupaten Seram Bagian Barat - Kubangun, Hamdani; Nis Wahyuni Pattimura (Jurnal Serambi Engineering, 2025)
The use of irrigation pumps is one of the key solutions in addressing the problem of water availability for agriculture, especially in areas with limited surface water sources. This study aims to analyze the effectiveness and efficiency of the use of irrigation pumps in improving agricultural productivity, taking into account pump power parameters, water discharge, and the area of paddy fields served. This study uses a quantitative approach by sampling irrigation pumps that have known specifications, namely 23.35 kW of pumping power, 200m3/s of water discharge, and 4 hectares of rice fields served. Data collection methods include direct field measurement, interviews with user farmers, and analysis of secondary data from relevant agencies. The results of the research show that with a pumping power of 23.35 kW and a water discharge of 200 m3/s, irrigation pumps are able to serve water needs for an optimal 4-hectare rice field area. The conclusion of this study confirmed that the use of irrigation pumps with appropriate specifications could significantly increase agricultural productivity and farmers' welfare. Recommendations for further research include optimization of pump irrigation system design and integration with precision agricultural technology to improve water and energy use efficiency.